2019
DOI: 10.33772/jitro.v6i2.5638
|View full text |Cite
|
Sign up to set email alerts
|

Review: Hidrogen Sianida dan Implikasinya pada Ternak

Abstract: ABSTRAK                                                            Sejumlah besar tanaman hijauan banyak mengandung glikosida sianogenik dandapat  dirombak menjadi hidrogen sianida (HCN) yang bersifat toksik. Hidrogen sianida dapat menyebabkan keracunan pada manusia dan hewan.Konsentrasi HCN dalam hijauan dapat diturunkan melalui beberapa metode pengolahan seperti pengupasan, pengeringan, fermentasi, pemotongan dan penyimpanan.Gejala klinis keracunan HCN pada ruminansia dapat berupa peningkatan pulsus, sesak n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…The drying process carried out by local farmers in the rainy season also becomes riskier to high humidity and low sunlight. This can result in a decrease of nutritional quality due to susceptible to mycotoxin contamination (Apata and Babalola, 2012;Penrith et al 2015;Yanuartono et al 2019;Penagos-Tabares et al 2021). A few cases have been reported that mycotoxin-causing fungi are very easy to grow in forage (Riet-Correa et al 2013;Gallo et al 2015;Palacio et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The drying process carried out by local farmers in the rainy season also becomes riskier to high humidity and low sunlight. This can result in a decrease of nutritional quality due to susceptible to mycotoxin contamination (Apata and Babalola, 2012;Penrith et al 2015;Yanuartono et al 2019;Penagos-Tabares et al 2021). A few cases have been reported that mycotoxin-causing fungi are very easy to grow in forage (Riet-Correa et al 2013;Gallo et al 2015;Palacio et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the symptoms caused by poisonous plants vary greatly, depending on the number of poisonous plants eaten and the content of toxic compounds in the plants. If not treated quickly will lead to death (Kennedy et al 2021;Yanuartono et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the crude sea cucumber extract (H.atra) produced foam which indicated that the saponin content was positive. According to Yanuartono et al (2017) Saponins have broad activities such as antibacterial and antifungal [10].…”
Section: Identification Of Secondary Metabolitesmentioning
confidence: 99%
“…Dosis letal pada pemberian untuk sapi dan domba kurang lebih 2 mg/kg bobot badan (Afrian, Liman, & Tantalo, 2014). Adanya HCN dalam bahan pakan dapat dikurangi jumlahnya melalui pengolahan dengan cara pelayuan atau pengeringan, perendaman pada air mengalir dan pemanasan (Yanuartono, Indarjulianto, Nururrozi, & Purnamaningsih, 2019).…”
Section: Pendahuluanunclassified